Grey’s Anatomy and Communication Accommodation: Exploring Aspects of Nonverbal Interactions Portrayed in Media - Jason T. Mickel; Shian-Li McGuire; Shelley Gross-Gray (Interpersona: An International Journal on Personal Relationships, 2013)
This study explores nonverbal communication measured in a television medical drama using the NAAS framework for investigating doctor-patient interactions viewed through the lens of communication accommodation theory. It aims to find how doctors in the television series Grey’s Anatomy exhibit a select set of nonverbal communication elements to accommodate their fictional patients. Of significance, the study draws attention to the impact of televised medical programs on real-life doctor-patient encounters, focusing on under-researched aspects of communication in this context. Eight episodes of the series Grey’s Anatomy were coded for four nonverbal behaviors during physician consultations with a single patient in each program. Only the first and last minutes of conversation were included in the analysis. Descriptive statistics demonstrate how doctors and patients behave in general across all episodes. A factor calculated from differences of proportions between patient and physician behaviors indicates whether doctors accommodate patients and consequently influence patient satisfaction. The analysis finds that the amount of nonverbal behavior between the parties was balanced, with doctors accommodating and not accommodating in equal frequency. The study discusses the implications not only on medical drama but also on the professional medical field, noting that television not only reflects real-life but also can establish communication expectations for better or worse. Utilizing the NAAS to understand how fictionalized interactions occur informs the medical community on how better to prepare doctors for patient communication.